Evaluation and Optimisation of Shirt Structure Design for Female Wheelchair Users (Journal of Fiber Bioengineering and Informatics, 2025)
The formal attire of female wheelchair users has received increasing attention in design research,particularly in response to unmet needs in professional settings. However, most existing studies focus oncasual or adaptive sportswear, leaving a significant gap in exploring clothing suitable for formal contexts.This study proposes a design method for optimising shirt prototypes for wheelchair users, incorporatingtwo key interventions: structural pattern adjustments and fabric innovation. The method was evaluatedthrough interviews with 51 participants. Conventional shirts often fail to accommodate the seatedposture, resulting in poor fit, restricted mobility, and discomfort. To address these issues, structuralmodifications were introduced to the armholes, sleeve caps, and plackets to enhance forward-reachingmobility and improve dressing convenience. Similarly, fabrics suitable for individuals with limited handdexterity were selected based on thermal-moisture comfort and usability criteria. Subjective evaluationsdemonstrated that the synergy between structural refinement and fabric selection significantly improvedarm mobility and comfort in a seated position. This study offers practical insights for inclusive formal weardesign, presenting a method that balances formal attire for female wheelchair users.